Training needs of judo practitioners regarding sport psychology - Rutkowska, K. (Journal of Combat Sports and Martial Arts, 2012)
Nowadays, cooperation of a sportsperson with a sport psychologist should be a standard practice, adopted already at the level of children and young people`s sport. Thus, what are the experiences of young people regarding cooperation with a sport psychologist? Do they know what such a specialist deals with? How do they imagine possible cooperation with him/her? The objective of the research was to diagnose the needs of sport practitioners in the area of sport psychology. The aim of the paper and the author`s research was to analyse the awareness of the place of psychology in sport of children and youth, as well as the need for mental training. Material and methods. The research covered 72 young Polish judo practitioners - 26 girls and 46 boys. The respondents were of various age and presented different levels of sport abilities. They were participants of international judo competitions for children and youth. Results. The majority of the respondents have not worked with a sport psychologist and do not know the scope of his or her professional competence. Moreover, almost ¾ of the respondents do not express the need for such cooperation. However, the analysis of selected areas in sport (especially differences in subjective experiences and behaviour at training and competitions) indicates that there are fields where urgent specialist intervention is required. Conclusions. The analysis of the results leads to the conclusion about the need to introduce preventive, educational and intervention measures, implemented simultaneously among children and young people practising sport, as well as among their coaches, parents and sport peer groups.